Impurity rejection in the nickel laterite leach system - Wang, Kai (Curtin University, 2012)
Atmospheric leaching (AL) of low-grade nickel laterite ores can produce a pregnant leach solution (PLS) containing significant amounts of impurities such as trivalent iron, aluminium and chromium ions. Purification of PLS by precipitation of the impurities with an alkaline reagent often causes an associated loss of nickel. This thesis documents an investigation of the physicochemical processes that occur during the precipitation of iron, aluminium and chromium from both synthetic and real nickel laterite AL leach liquors and associated nickel losses.A chemical equilibrium model in the Fe(III)–Ni(II)–H2SO4–H2O system was developed with the effects of ionic strength and temperature taken into account. This model was able to calculate the concentration distribution of iron and nickel species over the pH range from 0 to 4 and temperature from 25 to 100 °C, and predict the pH value of the solution. In addition, the model can calculate the saturation index of iron oxides such as goethite, ferrihydrite and schwertmannite to predict whether a specific iron oxide will precipitate or dissolve under particular conditions. The solubility of goethite, ferrihydrite and schwertmannite decreased substantially with increasing pH value. Goethite, ferrihydrite and schwertmannite were all undersaturated below pH 2. With increasing pH, ferric ions tended to precipitate first in the form of ferrihydrite followed by goethite and schwertmannite. A mixture was formed above pH 2.5, of which schwertmannite was the dominant phase.Considerable effort has been put into the experimental study on the relationships between impurities removal and nickel losses from nickel laterite AL liquors. The precipitation experiments were conducted in either single- or multi-stage simulation using synthetic and real PLS. For the single-stage precipitation experiments conducted using a synthetic PLS containing Fe(III)+Ni(II), the effects of the factors governing the iron precipitation process upon nickel losses were investigated by statistical analysis and modelling. Temperature, pH and the initial Fe/Ni ratio in PLS were found to be the important factors affecting iron removal efficiency and the level of nickel loss to solid. These factors were studied using a three-level Box-Behnken design combined with response surface methodology. Quadratic models were fitted to the experimental data, to enable construction of 3D response surfaces and corresponding contour plots. These graphs clearly demonstrated the links between responses and the interactions of factors.Further single-stage precipitation experiments performed using PLS containing Fe(III)+Ni(II)+Al(III), Fe(III)+Ni(II)+Cr(III), and Fe(III)+Ni(II)+Al(III)+Cr(III) showed that greater losses of nickel to solids occurred in the presence of aluminium and chromium. Increasing the pH value of solution and precipitation temperature favored the removal of iron, aluminium and chromium, but at a cost of greater nickel losses. By carefully controlling pH and temperature using a multi-stage precipitation process, however, the iron, aluminium and chromium can be effectively rejected with a minimal nickel loss and desirable sludge properties. The optimum conditions for a multi-stage precipitation process were found to be at pH 3 and 55 ºC in the first stage followed by a second stage operated at pH 3 and 85 ºC. Using this precipitation procedure, as much as 95% iron and chromium together with above 80% aluminium can be removed; the level of nickel loss to the solid can be reduced to below 1%. The sludge showed a fast settling rate of 5.05 m/h with the addition of a cationic flocculant. Similar satisfactory results were also obtained when performing this multi-stage precipitation procedure on real leach solutions.The effect of water salinity on impurities removal and nickel losses was also examined due to variable nature of process water available in Western Australia to process nickel laterite during atmospheric leaching. This was achieved by conducting single-stage precipitation experiments in Fe(III)+Ni(II)+Al(III)+Cr(III) systems with various amounts of sodium chloride added. The presence of high concentration of salts resulted in higher removal efficiencies for iron, aluminium and chromium, and less nickel losses to the solids, particularly when the precipitation reactions were carried out at 85 ºC. XRD analysis of the residues confirmed that the poorly structural-ordered schwertmannite and/or ferrihydrite were the dominant phases. Natrojarosite (NaFe3(SO4)2(OH)6) can be detected when the precipitation reaction was conducted at pH 2 and 85 ºC from synthetic solution with high salinity.The presence of large amounts of poorly structural-ordered schwertmannite and ferrihydrite in the iron-rich residues complicates mineralogical identification using routine XRD technique. A comprehensive characterization was performed using a combination of several techniques that include selective Acidified Ammonium Oxalate (AAO) dissolution, differential XRD, SEM and FTIR spectroscopy. These techniques in combination allowed reliable mineralogical identification for samples containing high proportions of schwertmannite and ferrihydrite. The effects of foreign metallic cations on the crystallization, dissolution behaviour and surface sulphate coordination were investigated. The results suggested that the presence of goethite in the precipitates can be identified after removing the schwertmannite and/or ferrihydrite. Nickel, aluminium and chromium retarded the transformations of schwertmannite and/or ferrihydrite to goethite, but aluminium and chromium supressed the formation of 6-line ferrihydrite. Also, aluminium and chromium influenced the symmetry of the sulphate absorbed onto the iron-rich precipitates. The structural order of the phases became less pronounced with the presence of foreign metallic cations, particularly aluminium and chromium. Aluminium and chromium can strongly stabilize iron-rich precipitates making these resistant to leaching by AAO solution. FTIR analysis confirmed the presence of goethite in the bi-metallic precipitates and suggested that the sulphate is present to a greater extent in lower symmetry environments.